LITERATUR REVIEW : MEDIA PEMBELAJARAN GAME UNTUK MENINGKATKAN MINAT BELAJAR IPS SISWA SD - Qodri Nur Rizqi, Fitrohtus; Edwita; Rahmi Darman, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The literature review aims to analyze and synthesize research findings on the use of game-based learning media to increase elementary school students' interest in learning. The research method used is a systematic literature review that identifies, evaluates, and interprets relevant research findings from 25 indexed articles and other credible academic databases from 2021 to 2026. The analysis shows that game-based learning media, especially board games and digital game-based learning, are consistent and significantly improve learning interest, learning motivation, and student engagement in elementary schools. Games create an interactive, enjoyable, and contextually meaningful learning experience that triggers intrinsic motivation in students. Board game variations such as Snakes and Ladders, adventure board games, and map board games have proven effective across various subjects, including IPS. The conclusion is that game-based media is a highly recommended learning strategy for elementary school teachers, especially in the implementation of the Merdeka curriculum, which emphasizes active, joyful, and student-centered learning